Epoxidation of olefins by cytochrome P-450 model compounds: mechanism of oxygen atom transfer. - Collman, J P (1984)
The mechanism of the Mn(III) porphyrin-catalyzed epoxidation of olefins by lithium hypochlorite is examined. The active oxidant is thought to be a high-valent manganese-oxo complex. It is shown that a relatively stable intermediate is reversibly formed upon interaction of the olefin and the oxo complex. The decomposition of this intermediate to Mn(III) porphyrin and epoxide is the rate-determining step of the catalytic cycle. Some analogies to the biochemical epoxidation of olefins catalyzed by cytochrome P-450 are discussed.